Relationships between adolescents' and parents' values and parents' answering behaviour - Casas, Ferran (Metodološki zvezki, 2010)
In this paper we set out a confirmatory factor analysis model relating the values adolescents and their parents aspire to for the child's future. We approach a problem when collecting parents' answers and analysing paired data from parents and their child: the fact that in some families only one parent answers, while in others both meet to answer together. In order to account for differences between one-parent and two-parent responses we follow a multiple group structural equation modelling approach. Some significant differences emerged between the two and one answering parent groups. We observed only weak relationships between parents' and children's values.
Keywords: Values; Vrednote; Otroci; child; Children; Parents; Starši; Factor analysis; Faktorska analiza; raziskave